Front Cover: Manufacturing Approaches of New Halogenated Agrochemicals (Eur. J. Org. Chem. 12/2022). Issue 12 (22nd March 2022) - Jeschke, Peter
Abstract : The Front Cover illustrates some representative halogen‐containing aryl or heteroaryl moieties of the latest generation of halogen‐containing agrochemicals introduced into the global crop protection market over the past 10 years, and development candidates for use as acaricides, insecticides, nematicides, herbicides, and fungicides together with their targets. In around 81% of the agrochemicals, a significant rise of fluorine atoms and "mixed" halogen atoms, for example one or more fluorine, chlorine or bromine atoms is detected. Photo courtesy of USDA ARS. More information can be found in the Review by P. Jeschke.